2021
DOI: 10.3390/biomedicines9091095
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated Diacylglycerol 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol in Autoimmune Arthritis and Interstitial Lung Disease in SKG Mice

Abstract: Acetylated diacylglycerol 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) is a lipid molecule from the antlers of sika deer that might reduce inflammation by effectively controlling neutrophil infiltration, endothelial permeability and inflammatory chemokine production. Therefore, we evaluated the modulatory effect of PLAG on arthritis and interstitial lung disease (ILD) in an autoimmune arthritis model. We injected curdlan into SKG mice and PLAG was orally administered every day from 3 weeks to 20 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A previous medical study has shown that in the course of ILD, the serum level of TNF-α, a key cytokine that causes lung tissue fibrosis, is elevated (19). TNF-α is an inflammatory factor that can further promote the proliferation and differentiation of fibroblasts by mediating inflammatory damage in alveolar epithelial cells, thus ultimately promoting the development of lung tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous medical study has shown that in the course of ILD, the serum level of TNF-α, a key cytokine that causes lung tissue fibrosis, is elevated (19). TNF-α is an inflammatory factor that can further promote the proliferation and differentiation of fibroblasts by mediating inflammatory damage in alveolar epithelial cells, thus ultimately promoting the development of lung tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%